2017
DOI: 10.1002/jmv.24948
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of MERS‐spike protein ELISA in algorithm to determine serologic evidence of MERS‐CoV infection

Abstract: The Centers for Disease Control and Prevention (CDC) algorithm for detecting presence of serum antibodies against Middle East Respiratory Syndrome coronavirus (MERS-CoV) in subjects with potential infections with the virus has included screening by indirect ELISA against recombinant nucleocapsid (N) protein and confirmation by immunofluorescent staining of infected monolayers and/or micro-neutralization titration. Other international groups include indirect ELISA assays using the spike (S) protein, as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…While we found that rN-ELISA has lower sensitivity compared to both rS1 and rS ELISAs in line with a previous report (Wang et al, 2016), it was recently suggested to have higher sensitivity compared to rS-ELISA across a wide range of OD values (Trivedi et al, 2017). This discrepancy could be explained by the small number of clinical samples especially from high-risk groups used in previous studies which could represent a limiting factor to actually validate these assays.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While we found that rN-ELISA has lower sensitivity compared to both rS1 and rS ELISAs in line with a previous report (Wang et al, 2016), it was recently suggested to have higher sensitivity compared to rS-ELISA across a wide range of OD values (Trivedi et al, 2017). This discrepancy could be explained by the small number of clinical samples especially from high-risk groups used in previous studies which could represent a limiting factor to actually validate these assays.…”
Section: Discussionsupporting
confidence: 77%
“…Serological detection of MERS-CoV antibodies (Abs) in patients is based on screening by indirect ELISA using MERS-CoV nucleocapsid (N) protein and confirmation by immunofluorescence assay (IFA) of MERS-CoV infected cells and/or microneutralization (MN) assay (Al-Abdallat et al, 2014). Indirect ELISA based on recombinant MERS-spike (S) ectodomain protein (amino acids 1-1297) was recently included in this algorithm (Trivedi et al, 2017). Other groups have also used several other assays such as S protein microarray, IFA staining based on cells expressing recombinant full length S protein, plaque reduction neutralization test (PRNT), MERS-CoV pseudoparticle neutralization (ppNT) assay, and indirect ELISA based on S1 recombinant protein (Perera et al, 2013;Reusken et al, 2013;Zhao et al, 2013;Hemida et al, 2014;Meyer et al, 2014;Fukuma et al, 2015;Grehan et al, 2015;Müller et al, 2015;Muth et al, 2015;Park et al, 2015;Chan et al, 2017).…”
mentioning
confidence: 99%
“…The highly immunogenic S and N viral proteins are widely used targets for serological tests and are found on all coronaviruses. Various approaches have been developed: serum neutralization assays [29], microarrays [30], or more recently ELISA confirmed by a microneutralization test [31]. All methods are technically complex and require a high level of expertise that restrict their use to a few highly specialized facilities.…”
Section: Indirect Serological Testingmentioning
confidence: 99%
“…Several serological assays have been developed for detection of anti MERS-CoV antibodies, notably against N protein or S protein. While NAAT-based testing is the gold standard for MERS-CoV diagnosis, serological assays have some advantages such as a less restricted time frame for antibody versus viral RNA detection, easier application in the field during an outbreak situation, and more economical application in animal testing (Fukushi et al, 2018;Meyer et al, 2014a;Trivedi et al, 2018). However, potential pitfalls of serological testing were exposed during the SARS-CoV outbreak, including the possibility of crossreactivity to antigens from other coronaviruses (Meyer et al, 2014a).…”
Section: Detecting Human Immune Responsementioning
confidence: 99%
“…Nevertheless, serological testing remains one of the approved methods for MERS-CoV case confirmation by both WHO and CDC (World Health Organization, n.d., 2018; Centers for Disease Control and Prevention, 2017). One recent validation study suggested that combination of indirect MERS-CoV N and S ELISAs in combination with confirmation by microneutralization assay can improve overall detection sensitivity and specificity (Trivedi et al, 2018). Another recent innovation suggests the possibility of using competitive ELISA rather than IgG/IgM ELISAs that rely on a species-specific secondary antibody (Fukushi et al, 2018).…”
Section: Detecting Human Immune Responsementioning
confidence: 99%